Penyuluhan dan Pembuatan Handsanitizer Berbasis Produk Hasil Hutan Non Kayu (HHBK) - Shintawati Shintawati; Dewi Ermaya; Vida Elsyana; Devy Cendikia; Dian Ayu Afifah; Livia Rhea Alvita (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The Dharma Wanita Group (DWP) of the Lampung Provincial Forestry Service is a group of wives of civil servants in the Lampung Province Forestry Service which consists of ± 200 people. The purpose of forming this group is to increase the knowledge and skills of group members in supporting the husband's duties and is expected to be able to develop activities that can improve the family economy. Production forests in Lampung Province have great potential in producing non timber forest product (NTFP) commodities such as candlenut, nutmeg, coffee, citronella oil and a little patchouli oil. Currently, the NTFP commodity is only sold to collectors and markets near the production site. To increase the added value of these commodities, it requires skills and knowledge of persons engaged in the forestry sector to develop NTFP-based commercial products. Therefore, members of the DWP of the Lampung Provincial Forestry Service intend to develop practical knowledge and skills in making NTFP-based commercial products such as hand sanitizer. The purpose of this activity is to provide information on knowledge and practice of technical skills in making hand sanitizer from citronella oil, patchouli oil and clove oil. The methods used in this activities are counseling, practice and discussion. The results show that 80% of the participants understand the physical and chemical properties , as well as the benefits of citronella oil, patchouli oil, and clove oil and, can make hand sanitizer based on the three NTFP products.